Тематические разряды аббревиатур в современном крымскотатарском языке - Белялова, Л.С. (Культура народов Причерноморья, 2013)
В статье рассматриваются разные типы аббревиатур современного крымскотатарского
языка, которые последние два десятилетия активно используются в языке крымскотатарских средств
массовой информации. Впервые разработана и предложена их тематическая классификация:
наименования научных организаций и подразделений, разного рода международных организаций,
названия государственно–административной системы и ее составляющих, наименования
телевизионных и радиоканалов, новостных сайтов, политических партий, общественных движений,
названия государственных образований и республик, наименования предприятий и организаций и др. У статті розглядаються різні типи абревіатур сучасної кримськотатарської мови, які
останні два десятиліття активно використовуються в мові кримськотатарських засобів масової
інформації. Вперше розроблено і запропоновано їх тематична класифікація: найменування наукових
організацій і підрозділів, різного роду міжнародних організацій, назви державно-адміністративної
системи та її складових, найменування телевізійних і радіоканалів, сайтів новин, політичних партій,
громадських рухів, назви державних утворень і республік, найменування підприємств і організацій та ін. The article discusses the different types of the abbreviations of the modern Crimean Tatar language,
which are widely used in the Crimean Tatar language media during the last two decades. Their thematic
classification is firstly developed and offered. The thematic levels are the names of the scientific organizations
and departments, various international organizations, the names of the public administration system and its
components, the names of the television and radio channels, the names of the news sites, the names of the
political parties and the social movements, the public entities, the names of the republics and countries, the
names of enterprises and different organizations, the names of the state-owned enterprises, the names of the
housing and utilities, the names of the enforcement agencies and the traffic police, the names of terms and items
of the computer engineering, the computer science and the programming etc.
In the modern Crimean Tatar language the productivity of the abbreviated method of the derivation is clearly
seen. Those independent words are of the fundamentally new structure and they form the special section of the
Crimean Tatar language derivational system.